Enhancing vocational students’ learning activeness through the implementation of problem-based learning - Satria Pangestu; Marsono Marsono; Erry Ersani; Sayit Anwar (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
This study investigates the effectiveness of Problem-Based Learning (PBL) in enhancing learning activeness among vocational students in the Light Vehicle Engineering subject. A participatory classroom action research design based on the Kemmis and McTaggart model was implemented over two cycles. Data on learning activeness were collected using structured observation sheets, while instrument validity and reliability were confirmed through SPSS v.26, with all items showing acceptable validity (r > 0.334) and Cronbach’s Alpha values of 0.65 and 0.77 for cycles 1 and 2. A minimum target of 75% learning activeness was established. Results revealed a substantial improvement, with student activeness rising from an average score of 14.4 (58%, medium category) to 19.9 (80%, high category). These findings demonstrate that PBL effectively promotes learning activeness and supports more engaging, student-centered vocational education practices. Keywords: Gaps, Problem Based Learning, learning activeness, vocational students   Implementation of Problem Based Learning (PBL) learning model to increase the learning activeness of vocational students   Abstract: Penelitian ini bertujuan untuk mengetahui efektivitas model pembelajaran Problem Based Learning (PBL) dalam meningkatkan keaktifan siswa SMK pada mata pelajaran kejuruan Teknik Kendaraan Ringan.  Penelitian ini merupakan penelitian tindakan kelas (PTK) partisipatif dengan menggunakan desain milik Kemmis & McTaggart yang dilakukan selama 2 siklus. Metode pengambilan data menggunakan lembar observasi. Pengujian instrumen dilakukan melalui Uji validitas dan reliabilitas menggunakan aplikasi SPSS v.26 yang dinyatakan valid dan reliabel. Validitas memperoleh nilai r lebih dari 0.334, sedangkan reliabilitas Alpha Cronbach’s siklus 1 r= 0,65; siklus 2 r=0,77. Selain itu peneliti menentukan target rata-rata keaktifan minimal 75%. Hasil keaktifan siswa dari siklus 1 didapatkan rata-rata skor sebesar 14,4 atau 58% dalam kategori sedang kemudian di siklus 2 memperoleh skor 19,9 atau 80% dalam kategori tinggi. Hal ini menunjukkan bahwa penerapan model pembelajaran Problem Based Learning efektif dapat meningkatkan keaktifan siswa dalam pembelajaran siswa SMK.